Caesarean section in second stage of labour: a commentary on principles and techniques - Archibong, Michael S.; Adenikinju, Wilson S.; Olayemi, Olaniyi J.; Amuda, Mariam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Caesarean section done at full cervical dilatation (second stage of labour) has been on the rise globally and comes with its own unique challenges and complications. This commentary highlights the peculiar challenges associated with caesarean section in second stage of labour and gives an overview on various principles to be followed and techniques to employ to reduce fetal and maternal morbidity.